2010
DOI: 10.1007/s00106-009-2059-0
|View full text |Cite
|
Sign up to set email alerts
|

Akute Gehörschäden durch extrem hohe Schalldruckpegel

Abstract: The bulletin for occupational disease no. 2301 in the annex of the Occupational Disease Act, noise-induced hearing impairment, ("Merkblatt zu der Berufskrankheit Nr. 2301 der Anlage zur Berufskrankheiten-Verordnung: Lärmschwerhörigkeit") states that sound events with an intensity exceeding 137 dB (C) may cause immediate mechanical damage to the inner ear. Up to now a distinction has been made between prevention and actual damage potential for the risks caused by sounds with extremely high peak levels. In the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Measuring the noise level related to airbag deployment revealed values well below threshold values published for ear injury in humans [22][23][24][25][26]. Therefore, it seems not mandatory to include noise level measurements into a standard.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Measuring the noise level related to airbag deployment revealed values well below threshold values published for ear injury in humans [22][23][24][25][26]. Therefore, it seems not mandatory to include noise level measurements into a standard.…”
Section: Discussionmentioning
confidence: 96%
“…Hodge and Garinther [21] concluded that a pressure of approximately 69 kPa can result in injury of internal organs (e.g., bleeding of the lung). With respect to acoustic trauma, numerous studies indicate that a noise level of 125 dB(A) can result in injury [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…15-30 dB über dem maximalen impulsbewerteten Schalldruckpegel liegen. Ein Knalltrauma ist erst ab Spitzenschalldruckpegeln von mehr als 150 (C peak ) denkbar [ 7 ] . Ein Knalltrauma kann durch einen Knall im Millisekundenbereich (1-3 ms) hervorgerufen werden (z.…”
Section: Akute Lärmtraumenunclassified
“…akutes Lärmtrauma und keinesfalls ein Knalltrauma. Ein Knalltrauma kann durch Knalle mit einem Spitzenschallpegel ab 150-160 dB (C) entstehen ( Liedtke 2010 ). Hier liegen die Lärmpegel weit unter dieser Schädigungsgrenze.…”
unclassified